The Role of Comics in Elementary School Science Education - Hong-Yii Phoon; Roslinawati Roslan; Masitah Shahrill; Hardimah Mohd. Said (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
Comic books can be and are produced mainly for science communication. Comics are more favorable to be read by the students as comics engaged students in reading compared to thick science textbooks. This study explored the role of comics as an aid in teaching elementary school science on the topic of ‘Plant Systems’ using an action research approach. A total of 18 Grade 5 students from one of the elementary schools in Brunei Darussalam participated in the study. A 15-page fully colored comic featuring a leaf fairy character called ‘Nym’ was utilized to teach the students alongside various activities about plants during the intervention lessons. A pre-test was administered prior to the lesson to establish their existing knowledge of the topic, and then a post-test administered after all the intervention lessons were completed. The results from the achievement scores analyzed between the pre- and post-tests indicated that the students’ knowledge on ‘Plant Systems’ improved significantly. The students were found to be interested, engaged and enthusiastic in the use of comics as revealed from the thematic analysis of the interviews. There are also vast potentials for comics to be used regularly to support learning in science-related classrooms.